European guideline on indications, performance, and clinical impact of hydrogen and methane breath tests in adult and pediatric patients: European Association for Gastroenterology, Endoscopy and Nutrition, European Society of Neurogastroenterology and Motility, and European Society for Paediatric Gastroenterology Hepatology and Nutrition consensus. Issue 1 (25th August 2021) - Hammer, Heinz F.; Fox, Mark R.; Keller, Jutta; Salvatore, Silvia; Basilisco, Guido; Hammer, Johann; Lopetuso, Loris; Benninga, Marc; Borrelli, Osvaldo; Dumitrascu, Dan; Hauser, Bruno; Herszenyi, Laszlo; et al.
Abstract: Introduction: Measurement of breath hydrogen (H2 ) and methane (CH4 ) excretion after ingestion of test‐carbohydrates is used for different diagnostic purposes. There is a lack of standardization among centers performing these tests and this, together with recent technical developments and evidence from clinical studies, highlight the need for a European guideline. Methods: This consensus‐based clinical practice guideline defines the clinical indications, performance, and interpretation of H2 ‐CH4 ‐breath tests in adult and pediatric patients. A balance between scientific evidence and clinical experience was achieved by a Delphi consensus that involved 44 experts from 18 European countries. Eighty eight statements and recommendations were drafted based on a review of the literature. Consensus (≥80% agreement) was reached for 82. Quality of evidence was evaluated using validated criteria. Results: The guideline incorporates new insights into the role of symptom assessment to diagnose carbohydrate (e.g., lactose) intolerances and recommends that breath tests for carbohydrate malabsorption require additional validated concurrent symptom evaluation to establish carbohydrate intolerance. Regarding the use of breath tests for the evaluation of oro‐cecal transit time and suspected small bowel bacterial overgrowth, this guideline highlights confounding factors associated with the interpretation of H2 ‐CH4 ‐breath tests in these indications and recommends approaches to mitigate these issues. Conclusion: This clinical practice guideline should facilitate pan‐European harmonization of diagnostic approaches to symptoms and disorders, which are very common in specialist and primary care gastroenterology practice, both in adult and pediatric patients. In addition, it identifies areas of future research needs to clarify diagnostic and therapeutic approaches. Abstract :